Solar Photovoltaic (PV) – Diesel Hybrid Mini-Grid Systems And Improving Electricity Access in Rural Ghana - Gyan-Amponsah, Kwabena Amponsah (2022)
Energy is an essential component of human lives and improving access to clean, affordable, reliable, and modern energy services, as is the objective of the Sustainable Development Goal (SDG) 7, is vital to the well-being of people and for socio-economic development. Despite the undoubted importance of energy, globally about 770 million people have no electricity access and 2.5 billion others are without access to clean fuels, thereby relying on traditional solid fuels as their primary source of fuels to meet their energy needs. The use of these traditional fuels has significant impacts on the health, social and economic development of the affected people and the environment. In the bid to achieve the objective of SDG 7 and improve the well-being of the affected global population, several interventions have been set up to address the energy access problem. However, these interventions have not been able to achieve their intended targets due to reasons such as the fact that energy access research and interventions have focused on the science, engineering, and economic dimensions of the problem with limited attention on the social and human dimensions, especially in the Sub-Saharan Africa context. For a comprehensive approach, further research to understand the impacts of socio-cultural practices of end-users such as traditions and behaviours, energy needs/priorities of the users, and energy behaviour is vital. Echoing the global energy access problem in Ghana, the research aimed to assess the social and cultural determinants of energy access in rural island communities in the Ada East district to better understand the feasibility of solar PV-diesel hybrid mini-grid systems for improving electricity access. The research adopted a mixed-method approach (surveys and interviews) to collect data on the energy needs of the research participants, the socio-cultural determinants of energy access, and the factors promoting and impeding the adoption of renewable energy technologies. The research adopted and applied Quinn et al.'s (2018) logic model for clean fuel scale-up to the adoption of Solar PV-diesel hybrid mini-grids for electricity access. The results showed that energy needs vary widely within households and communities, and these are impacted by demographics and socio-cultural practices such as energy priorities, gender roles, and intrahousehold decision-making, among others. The research further revealed that to ensure the sustainability of projects and interventions to improve access to modern energy services, there is a need to adopt a “bottom-up” approach to ensure that the needs and concerns of end-users are given adequate consideration. The research is the first to apply Quinn et al.'s (2018) model on clean fuel scale-up to the adoption of renewable energy technologies and establish that it is applicable albeit with some adaptations. The research contributed to the gaps in the literature on energy access by showing the linkages between different age groups and household energy access as well as showing that differences in intrahousehold energy needs and priorities significantly influenced energy choices and decisions. The research also explored the impact that end-user perception has on the willingness to adopt renewable technology and the successful implementation of renewable energy projects in general.